Ambientes contrastantes de luz alteram a relação entre taxas demográficas e características fotossintéticas em mudas de espécies arbóreas tropicais? - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Functional traits have been used to explain demographic rates of forest stands at different site conditions. However, weak or nonexistent relationships have often been found, especially due to a lack of consideration of the environmental context, the neglect of intraspecific variation and poor explanation capacity of selected traits. Furthermore, the effects of environment light availability on the relationship between functional traits, growth and survival are still not well understood. Analyzing how light availability influences the demographic rates-functional traits relationship is important for a better understanding of the main mechanisms that control the dynamics of the forest. In this study, the objective was to investigate whether contrasting light conditions alter the relationship between demographic rates and photosynthetic traits during the initial establishment of a forest stand. The study was carried out in a secondary forest enrichment plantation, located at the UFAM experimental farm. In March 2017, seedlings of six forest species (Cedrela fissilis, Tabebuia rosea, Swietenia macrophylla, Bertholletia excelsa, Carapa guianensis and Hymenaea courbaril) were planted under different conditions of canopy opening resulting from the application of thinning treatments with different levels of basal area reduction in canopy trees and removal of plants from the understory. In the present study, plots with total removal of the basal area (full sun) and with no removal of the basal area (understory) were selected, both with the removal of the natural vegetation of the understory. Seedling growth and survival rates were calculated two years after planting, together with the measurement of a range of crown (e.g. crown projection area, crown length), morphological (e.g. total leaf area, specific leaf area, leaf dry matter content) and physiological (e.g. chlorophyll pigments content, fluorescence of chlorophyll a and gas exchange) traits. Overall, the relationships, in models with a single trais, were more strength at full sun (R2 m = 0.03 – 0.47) than at understory (R2 m = 0.03 – 0.33). Even though the crown projection area, crown length, total leaf area and total maximum photosynthetic rate have had the strongest relationships in both environments, the full sun environment had a greater number of related traits. An analysis at the individual-level resulted in the largest number of significative relationships between demographic rates and photosynthetic traits. Finally, the ability to predict growth rates from photosynthetic traits is improved when analyzed in models with multiple traits, both in full sun (R2 m = 0.20 – 0.57) and in the understory (R2 m = 0.03 – 0.48).
Keywords: Ecofisiologia vegetal - Amazônia; Fotossíntese - Amazônia; CIÊNCIAS AGRÁRIAS; Ecofisiologia; Crescimento; Sobrevivência; Características funcionais; Irradiância; Fotossíntese; Fluorescência; Amazônia Central